Intrinsic and extrinsic motivation towards the employee intention to stay in the organization : A case study at three hotel in Kota Kinabalu / Mohd Al Amin Abdul Thani and Mohd Nazri Jahri - Abdul Thani, Mohd Al Amin; Jahri, Mohd Nazri (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
Motivation is important because it will lead the personnel to perform better but if they feel de-motivated then the personnel will become inefficient or unproductive and at the same time it will decrease the work performance and high rate of turnover will occur. Therefore, this study focuses on determining and knowing whether the intrinsic and extrinsic motivation has an effect on the employee's loyalty towards their organization. A random sample of 105 respondents focusing in Kota Kinabalu City was being studied by gaining their feedbacks regarding their motivation factor. Not surprisingly, the percentage of being high loyalty and average loyalty was almost the same by only having slight differences. The motivational factors among the employees around Kota Kinabalu City were still need to be taken into consideration and seriously in order for them to stay loyal with their organization.